American dharma : Buddhism beyond modernity - Gleig, Ann (Yale University Press, 2019)
"The past couple of decades have witnessed Buddhist communities both continuing the modernization of Buddhism and questioning some of its limitations. In this fascinating portrait of a rapidly changing religious landscape, Ann Gleig illuminates the aspirations and struggles of younger North American Buddhists during a period she identifies as a distinct stage in the assimilation of Buddhism to the West. She observes both the emergence of new innovative forms of deinstitutionalized Buddhism that blur the boundaries between the religious and secular, and a revalorization of traditional elements of Buddhism, such as ethics and community, that were discarded in the modernization process. Based on extensive ethnographic and textual research, the book ranges from mindfulness debates in the Vipassana network to the sex scandals in American Zen, while exploring issues around racial diversity and social justice, the impact of new technologies, and generational differences between baby boomer, Gen X, and millennial teachers."--Provided by publisher